THE EFFECT OF RADEC MODEL AND EXPOSITORIAL MODEL ON CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL STUDENTS IN SURALAYA (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This study aims to examine differences in the level of creative thinking of students who follow the learning with RADEC and Expository learning model. The population in this study were all elementary students in Pagerageung sub-district and Sukaresik sub-district of Suryalaya district, West Java province. The sample of the study was 120 students who were taught by eight teachers who had attended the RADEC learning workshop and applied it in school. Data collection techniques used in this study consisted of observation, and documentation. Data analysis techniques used are different test or t-test. The results showed that learning by RADEC model statistically significant effect on the increasing ability of student creative thinking. This is evidenced from the significance of Sig. (2-tailed) in Equal variances not assumed shows a value of 0.007 and this value is smaller than ? = 0.05. Therefore, it can be concluded that H0 is rejected and H1 is accepted. That is, the hypothesis that there is a significant difference in the creative thinking ability of students who follow the learning with RADEC and Expository learning model is acceptable.